From preparation to product: Factors influencing probiotic viability in spray drying - Sin, Phin Yin; Tan, Suat Hian; Mohd Fazli, Farida Asras; L. U., Karmawan (Penerbit Universiti Malaysia Pahang, 2024)
With growing health awareness, particularly amid the SARS-CoV-2 pandemic, consumers increasingly value nutrition, diet, and food safety. Probiotic-based foods and beverages are widely recognized for their health benefits, including improved gut health and immune function. Spray drying is a scalable and efficient method for encapsulating, enhancing the stability and shelf life of probiotics. This review explores strategies to optimize the spray drying process, with a particular focus on factors influencing probiotic viability during and after drying. Key considerations included strain-specific thermal tolerance, feed composition, and critical process parameters such as drying temperature and feed rate. Notably, encapsulating agents play a vital role in maintaining the physicochemical quality of the final product while protecting probiotics from environmental stress. Recent advancements in encapsulation technologies, including biopolymers, hybrid materials, and emerging nanotechnology-based solutions have shown significant potential for enhancing probiotic survival under harsh processing conditions. Future research should integrate molecular-level insights, such as omics-based approaches, to better understand stress responses and optimize encapsulation strategies. Genome-editing tools and high-throughput screening techniques could accelerate the creation of thermotolerant probiotic strains, enabling more robust formulations. In parallel, the development of environmentally sustainable encapsulating agents with superior protective properties is essential to advance both efficiency and scalability. By addressing these challenges, spray drying can be further refined to produce durable, high-quality probiotic formulations that meet the growing demand for functional foods and beverages, while aligning with evolving consumer health priorities.